Outcome of Left Anterior Descending Coronary Artery Ostial Lesions Treated with Drug-Eluting Stents: Coronary Artery Ostial Lesions Treated with Stents - Abbasi, Muhammad Afzal; Kamran, Rana M. Haseeb; Minhas, Amjad; Rehman, Adeel Ur; Kashmir, Saba Binte; Saif, Izza (Pakistan Journal of Health Sciences, 2024)
Patients with severe Left Main Stem (LMS) stenosis have very high risk of major cardiovascular events because of the extent of myocardium suffering ischemia. Coronary artery disease of left main stem is not very common but key cause of characteristic coronary artery disease. Such stenosis is usually treated with CABG which is the gold standard treatment. Objective: To determine the outcome of left anterior descending coronary artery ostial lesions stenting with drug-eluting stents. Methods: The descriptive case series was conducted at a teaching hospital in Lahore, from 01-08-2019 to 29-07-2020. After informed consent 113 patients were included in study; both genders and diagnosed cases of LAD ostial disease, keeping in view inclusion and exclusion criteria. Then patients were admitted in cardiology wards after recording demographic data. Next day, the patients underwent angioplasty under local anesthesia. After procedural success patients were followed-up there for 3 days to assess if there was repeat myocardial infarction or mortality within hospital stay. All information obtained was recorded on a standard performa. Quantitative and qualitative data were analyzed and outcome of the procedure was recorded. Results: In our study 104(92.04%) patients were male and 9(7.96%) patients were females. The Drug-Eluting Stents (DES) procedural success was found in 93.81% patients, post stenting MI observed in 6.4% patients and the mortality occurred in 2.7% patients. Conclusions: The left anterior descending coronary artery ostial lesions stenting with DES is effective and feasible procedure with good outcome.